The industrial waste landfills – challenges regarding the siderurgical slag dumps located in Hunedoara municipality - Kiss, Imre; Alexa, Vasile (JOURNAL OF LANDSCAPE ECOLOGY, 2014)
Currently, approximately five percent of Hunedoara county area, Romania (Vajdahunyad [hu], Eisenmarkt [ge]), is occupied by industrial landfills. In case of dumps, such as the siderurgical slag dump located in Hunedoara, the slags can be recycled even for road building. Regarding the slag dumps located in the area of former mines, where the materials (complex ores) cannot be reused, they remained abandoned pending for greening projects. For now, the greening price exceeds the possibilities, and the environmental issues persist in these areas. But, although were repeatedly discussed about the possibility of using the slag, nothing happened on a large scale until now. The paper presents an assessment of wastes recycling potential from siderurgical slag dumps. Therefore, the companies that make highways must include in their projects the option of using tailings if they aim the economic performance, because the alternative of using stone from quarries is more expensive, increasing the price of the works. There are many economic arguments, the most important being the reduction of expenses required for building one kilometre of highway, which impose the use of these type of slags instead of ballast for the construction of highways.
Keywords: siderurgical slag dumps; industrial waste landfills; waste management